Gut CD4+ T cell phenotypes are a continuum molded by microbes, not by TH archetypes - Kiner, Evgeny; Willie, Elijah; Schmutz, Hugo; Chandler, Jodie; Schnell, Alexandra; Thakore, Pratiksha I.; LeGros, Graham; Mostafavi, Sara; Benoist, Christophe; Aguilar, Oscar; Allan, Rhys; Astarita, Jilian; et al. (Nature Immunology, 2021)
CD4+ effector lymphocytes (Teff) are traditionally classified by the cytokines they produce. To determine the states that Teff cells actually adopt in frontline tissues in vivo, we applied single-cell transcriptome and chromatin analyses to colonic Teff cells in germ-free or conventional mice or in mice after challenge with a range of phenotypically biasing microbes. Unexpected subsets were marked by the expression of the interferon (IFN) signature or myeloid-specific transcripts, but transcriptome or chromatin structure could not resolve discrete clusters fitting classic helper T cell (TH) subsets. At baseline or at different times of infection, transcripts encoding cytokines or proteins commonly used as TH markers were distributed in a polarized continuum, which was functionally validated. Clones derived from single progenitors gave rise to both IFN-γ- and interleukin (IL)-17-producing cells. Most of the transcriptional variance was tied to the infecting agent, independent of the cytokines produced, and chromatin variance primarily reflected activities of activator protein (AP)-1 and IFN-regulatory factor (IRF) transcription factor (TF) families, not the canonical subset master regulators T-bet, GATA3 or RORγ.
CRIS-Team Scopus Importer:2023-10-02